Discovering Saudi Arabia's Cultural and Economic Legacy Through Coffee - Maspul, Kurniawan (Indonesian Journal Publisher, 2025)
Coffee in Saudi Arabia is far more than a beverage; it is a vibrant tapestry of heritage, social cohesion, and economic ambition. This study examines the profound interplay between coffee (qahwa) and Saudi identity, tracing its historical roots from 15th-century trade routes to its modern-day role as a pillar of cultural and economic resilience. Through a mixed-method approach—including qualitative interviews, ethnographic observations, and literature analysis—the research unveils how coffee rituals, such as the Bedouin Ghawah ceremony, embody symbolic interactionism and communitas, fostering trust and unity in a collectivist society. Over 94% of Saudi households uphold coffee hospitality as a moral obligation, while 72% of youth frequent coffeehouses (maqha) weekly, bridging generational divides. Economically, the sector thrives as a Vision 2030 priority: the 1.54 billion market grows at 5.12% annually, with the Saudi Coffee Company targeting 2,500 tons of domestic production and 8,000 jobs by 2030 (Statista, 2025; PIF, 2022). UNESCO’s 2021 recognition of Arabic coffee as Intangible Heritage underscores its global legacy, while sustainable practices and coffee tourism offer pathways for economic diversification. Policymakers, economists, and cultural custodians will find here a blueprint for harmonizing heritage with progress, ensuring that every cup of qahwa brews a future as rich as its past.